Differentiation of Sclera in Chick Embryo at Various Stages of its Development- A Histological Study - Ruqqia Shafi Minhas, Sadia Shaukat, Hina Kundi, Saima Sohail, Amaidah Mir, Abdullah Qamar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The sclera is the outer strong opaque covering of the eye that functions as protective layer and provides site for attachment of extra ocular muscles. Aim: To study the microscopic anatomy of sclera in chick at various stages of embryological development keeping in mind the practical application of this information in understanding human development and disease processes. Methodology: It was an experimental study. The study was carried out at department of Anatomy, CPSP Regional Centre, Islamabad. Eyeballs were collected from group A, B and C (n=30 each) on day 10, 12 and 15 of incubation respectively. Dissected out tissues were processed and stained with Hematoxylin & Eosin and Alizarin red. The prepared specimens for group A and C were analysed under light microscope while the specimens from group B were observed via stereomicroscope. Data was evaluated by using SPSS version 23. Independent t-test was applied with p-value of less than 0.05 was considered significant. Results: As the chondrocytes in cartilaginous layer of sclera became mature, they change their shape from flattened to more rounded cells. The proteoglycan content in the cartilaginous matrix increased. The mean number of chondrocytes increased from 17.4 ±1.4/unit area on day 10 to 10.0 ±0.8/unit area on day 15. The mean thickness of cartilaginous layer increased from 44 ±2.4µm on day 10 to 77 ±8.3 µm on day 15 of development. Calcification of scleral ossicles became obvious at about 12 days of incubation when seen under stereomicroscope. Practical Implication: This study highlighted that understanding for the development of scleral elements (understudied tissue of the eye) can be critical in research involving autoimmune diseases and neural crest defects. Considering similar developmental stages among humans as in chick embryo. Conclusion: It was concluded that growth of sclera in eye of chick has been indicated by increase in thickness of its layers and increase in the number of chondrocytes/unit area and progressing calcification of ossicles in its bony part. Keywords: Chick Embryo, Chondrocytes, Hyaline Cartilage and Ossicular Ring.